Focus on form and L2/L3 English teaching - Saraiva Pasca, Maria Alejandra; Spinassé, Karen Pupp (BELT - Brazilian English Language Teaching Journal, 2017)
Grammatical and lexical similarities between languages can help promote adult language learning. However, even when learners are provided with a lot of input in the L2, they may not notice certain similarities and differences between their L1 and the L2 in the classroom if the linguistic structure is not salient. The purpose of this article is to discuss the benefits of making grammatical and lexical comparisons among languages, such as proposed in the EuroCom Project, and the importance of using a Meaning and a Form Focused Instruction with corrective feedback when teaching L3 learners, based on different studies carried out with multilinguals. The more the Brazilian learners of English as a second or third language notice the similarities among English, Spanish and Portuguese, the more advantage they will take of their prior linguistic knowledge, facilitating the L3 learning process.